Human Trafficking in the Lens of Liberalism in International Relations - Naeli, Fitria (Westscience Press, 2025)
Human trafficking has garnered significant global attention as one of the most pressing issues impacting hundreds of millions of individuals worldwide. It poses a severe threat to human rights and international security, necessitating urgent and coordinated responses. Examining this issue through the lens of liberalism in international relations underscores the shortcomings of global cooperation and institutional frameworks, particularly in upholding normative values designed to safeguard individual freedoms and promote global justice. Within contemporary migration discourse, human trafficking must be recognized as an integral component of the debate. Various international instruments, such as the United Nations Protocol on preventing, suppressing, and punishing trafficking in persons, along with regional agreements, reflect the liberalist ideal of institutional collaboration in combating these transnational crimes. However, the persistence of human trafficking in many countries can be attributed to weak governance, socio-economic disparities, and insufficient enforcement mechanisms, challenging the liberalist assumption that progressive cooperation naturally mitigates such issues. Civil society organizations and advocacy networks serve as influential lobbying entities, exerting pressure on governments to uphold international norms and implement effective anti-trafficking measures. These groups play a critical role in fostering education, empowerment, and cross-border cooperation to address the root causes of trafficking. From a liberalist perspective, the emphasis on eradicating human trafficking rests on the necessity of multilateral collaboration, the establishment of strong legal frameworks, and the reinforcement of shared global values. Ensuring the protection of individual freedoms is foundational in the broader strategy to eliminate human exploitation. This perspective highlights the intersection between normative commitments and practical mechanisms, emphasizing the need for comprehensive, coordinated efforts to confront one of the most urgent humanitarian crises of the 21st century.